Integrating benthic habitat indicators: Working towards an ecosystem approach. (April 2018) - Elliott, Sophie A.M.; Guérin, Laurent; Pesch, Roland; Schmitt, Petra; Meakins, Bryony; Vina-Herbon, Cristina; González-Irusta, Jose M.; de la Torriente, Ana; Serrano, Alberto
Abstract: The Marine Strategy Framework Directive (MSFD) requires an ecosystem-based approach to assess the state of Europe's seas. To date, assessment is carried out on an indicator by indicator basis. Integration of indicators is required to undertake a more holistic assessment of the state of the marine environment. Here, an integrated approach to assess benthic habitats is proposed. Within this conceptual method, four OSPAR benthic habitat indicators relating to biodiversity (D1) and sea-floor integrity (D6) descriptors are linked together. For the integration, benthos, environmental and anthropogenic pressure data are required. State indicators are assessed along a gradient of pressure to facilitate threshold values to be quantified and provide advice on management measures. The method also includes a feedback system whereby best available evidence on benthos, its sensitivity and disturbance assessments can be replaced with ground-truthed data. The proposed method can be expanded to include other related indicators under the different descriptors (e.g. commercial fish and shellfish (D3), food webs (D4) and eutrophication (D5)) where relevant. The concept is a first step towards integration of benthic indicators and could be applied to monitoring requirements under other Directives such as the Habitat or Water Framework Directive. Highlights: Indicator integration is essential for the assessment of GES under the MSFD. A quantitative approach to integrate benthic indicators assessment is proposed. Pressure-state analysis is used to understand threshold tipping points. The proposal enables quantitative MSFD management recommendations.